TAKSONOMI TUMBUHAN OBAT DI DESA RIANG BANDUNG KECAMATAN MADANG SUKU DUA OKU TIMUR - Rosanti, Dewi (Faculty of Mathematics and Natural Science, Universitas PGRI Palembang, 2014)
Research of taxonomy of fitopharmaca species was conducted at Riang Bandung village in Madang Suku Dua Recency, Sumatera Selatan Province on June till July 2013. The objective of this research was Plant had fitopharmaca potency. This research utilited the direct observation with around research location during two weeks. The result of the research gated 1 division, 2 class, 10 order, 10 family, 13 genera and 14 species as Imperata cylindrica , Curcuma domestica, Zingiber officinale, Alpinia galanga, Carica papaya, Citrus aurandifolia, Cinnamonum zeylanicum, Annona muricata, Piper betle, Piper nigrum, Jatropa curcas L. , Manihot utilisma, Psidium guajava L., dan Justicia gandarussa. Key words: taxonomy, fitopharmaca